1975
DOI: 10.1104/pp.56.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cytokinin in Bacterial Leaf Nodules of Psychotria punctata (Rubiaceae)

Abstract: MATERIALS AND METHODSCytokinin activity based on two bioassays was at least 100-fold higher in Psychotria punctata leaf discs with bacterial nodules than in discs without them. Nodulated discs from young leaves yielded 0.4 to 6 pg of cytokinin (zeatin equivalents) per g fresh weight of leaf tissue, whereas nonnodulated discs from the same leaves yielded 0 to 0.003 pg per g fresh weight. These estimates probably include free-base cytokinins and, if present, any nucleoside cytokinins precipitable by acidic silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The oat leaves remained green under the nodulated disks, indicating cytokinin activity. Analysis of the contents of Psyeliotria nodules for the presence of cytokinins showed that cytokinin activity was 100 times greater in the nodules than in regular leaf tissue (Edwards & LaMotte, 1975), These workers eoneluded that this leaf nodule association was most probably a cytokinin-mediated symbiosis. The question of what is being transferred from the bacterial symbiont to the host yam is yet to be answered, but seems likely to be a eompound affecting host-plant development.…”
Section: Discussionmentioning
confidence: 99%
“…The oat leaves remained green under the nodulated disks, indicating cytokinin activity. Analysis of the contents of Psyeliotria nodules for the presence of cytokinins showed that cytokinin activity was 100 times greater in the nodules than in regular leaf tissue (Edwards & LaMotte, 1975), These workers eoneluded that this leaf nodule association was most probably a cytokinin-mediated symbiosis. The question of what is being transferred from the bacterial symbiont to the host yam is yet to be answered, but seems likely to be a eompound affecting host-plant development.…”
Section: Discussionmentioning
confidence: 99%
“…The notable investment in the formation and vascularization of leaf nodules and the pleomorphism of the bacteria in leaf nodules also infer that the symbionts have beneficial functionality (Miller et al 1978(Miller et al , 1983a(Miller et al , 1983b. To date, most of the functions proposed are related to the nutrition and growth regulation of the plant hosts, including nitrogen fixation (Von Faber 1914;Hanada 1954;Yamada 1960;Bettelheim et al 1968) and production of IAA (Yamada 1960) and cytokinins (Becking 1971;LaMotte and Lersten 1972;Rodrigues Pereira et al 1972;Edwards and LaMotte 1975). It has been claimed that removal of leaf-nodule bacteria could cause distorted leaf formation and that the growth regulators produced by the isolated symbionts could rescue the symptoms in newly formed leaves; however, such results are problematic because they are based on questionable identification and isolation of the bacteria (Miller 1990).…”
Section: Functionality Of Symbiontsmentioning
confidence: 99%
“…Microorganisms involved in beneficial interactions with plants, either as intracellular symbionts or endophytic colonizers, usually perform tasks for the host plant which may include nitrogen fixation or nutrient uptake (phosphorus, metals). Finally, the obligate nature of the symbiosis and the stunted appearance of the symbiont-free Psychotria seedlings have given rise to the notion that the bacteria participate to the host's hormone metabolism (Edwards and Lamotte, 1975;Van Oevelen et al, 2003). Participation in mineral uptake is unlikely, since the bacterial symbionts are restricted to the leaves.…”
Section: Absence Of Genes Traditionally Associated With Plant Symbiosesmentioning
confidence: 99%
“…We could not find any genetic evidence of diazotrophy in the P. kirkii leaf symbiont, thereby giving further support to the view that nitrogen fixation is not a function of the Psychotria/Burkholderia leaf symbiosis. Finally, the obligate nature of the symbiosis and the stunted appearance of the symbiont-free Psychotria seedlings have given rise to the notion that the bacteria participate to the host's hormone metabolism (Edwards and Lamotte, 1975;Van Oevelen et al, 2003). We performed tBlastn searches using various wellannotated prokaryotic and eukaryotic protein sequences shown to be involved in phytohormone biosynthesis or degradation (Table S3).…”
Section: Absence Of Genes Traditionally Associated With Plant Symbiosesmentioning
confidence: 99%